The Effectiveness of The Implementation of Bengkalis Regency Regional Regulation Number 3 of 2022 in The Payment of Workers’ Wages - Oktaviani, Belinda; Tan, Winsherly; Situmeang, Ampuan (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
Research on the effectiveness of the implementation of Bengkalis Regency Regional Regulation Number 3 of 2022 concerning the provision of wages for local workers is conducted to ensure that the payment of wages to local workers in Bengkalis Regency complies with the applicable laws and regulations, while also promoting the welfare of its workforce. The provision of fair and timely wages, along with supporting welfare facilities, remains an issue that has not yet been fully realized in Bengkalis Regency. Various factors influence the effectiveness of this regulation in ensuring the proper payment of wages to local workers. Therefore, this study examines five factors influencing legal effectiveness as proposed by Soerjono Soekanto and reviews the implementation of wage distribution for local workers in Bengkalis Regency by employers. In addition to employers, the regional government  through collaboration between the Regent and other local institutions, such as the Department of Manpower and Transmigration of Bengkalis Regency and the Technical Implementation Unit of Manpower, can play a a role in taking preventive and repressive measures to achieve the effectiveness of Bengkalis Regency Regional Regulation Number 3 of 2022 (Perda Kab. Bengkalis No. 3/2022. This study further identifies the causes of non-compliance in wage provision for local workers and proposes solutions to ensure the objectives of the regulation can be met. Accordingly, the solutions offered by this research aim to provide stronger protection for local workers in Bengkalis Regency and to advance the welfare of the local community. [Penelitian mengenai efektivitas penerapan Peraturan Daerah Kabupaten Bengkalis Nomor 3 Tahun 2022 terhadap pemberian upah tenaga kerja lokal dilakukan agar pembayaran upah tenaga kerja lokal di Kabupaten Bengkalis dapat sesuai dengan peraturan perundnag-undangan yang berlaku dan memberikan kesejahteraan bagi tenaga kerjanya. Pemberian upah tenaga kerja yang sesuai dan tepat waktu serta fasilitas penyokong kesejahteraan lainnya menjadi hal yang masih belum dilakukan di Kabupaten Bengkalis. Banyak faktor yang mempengaruhi efektivitas pelaksanaan Perda ini dalam pemberian upah tenaga kerja lokal yang sesuai, sehingga penelitian ini akan mengkaji 5 faktor yang mempengaruhi efektivitas hukum milik Soerjono Soekanto dan meninjau pelaksanaan pemberian upah tenaga kerja lokal di Kabupaten Bengkalis oleh pengusaha. Bukan hanya pengusaha, pemerintah daerah melalui kerja sama Bupati dan perangkat-perangkat daerah lainnya, seperti Dinas Ketenagakerjaan dan Transmigrasi Kabupaten Bengkalis dan Unit Pelaksana Teknis Ketenagakerjaan dapat berperan dalam mengambil langkah preventif dan represif agar efektivitas pelaksanaan Perda Kab Bengkalis No. 3 Tahun 2022 dapat tercapai. Dalam penelitian ini, penyebab dari pemberian upah tenaga kerja lokal masih banyak yang tidak sesuai akan diberikan solusi agar harapan dari Perda ini dapat tercapai. Maka, solusi-solusi yang diberikan dari penelitian ini akan melindungi tenaga kerja lokal di Kabupaten Bengkalis lebih baik dan mencapai kesejahteraan masyarakat di Kabupaten Bengkalis.]